THE ROLE OF E-SERVICE QUALITY AND ELECTRONIC WORD OF MOUTH IN SHAPING BRAND IMAGE AND REPURCHASE INTENTION AMONG LAZADA USERS IN PEKANBARU - Rahman, Sarli; Aprila, Bord Nandre; Novrizal, Dedy; Martias, Fery; Prabowo, Muhammad Panji (Institut Bisnis dan Teknologi Pelita Indonesia, 2025)
The rapid growth of online shopping platforms has intensified competition among e-commerce providers, emphasizing the importance of delivering high-quality digital services and fostering effective electronic communication to strengthen brand image and retain customers. This study investigates the influence of e-service quality and electronic word of mouth (e-WOM) on brand image and repurchase intention among Lazada users in Pekanbaru. A quantitative approach was employed, involving 300 respondents who had used the Lazada platform within the last one to three months. Primary data were collected through a structured questionnaire and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The findings reveal that e-service quality has a positive and significant effect on both brand image and repurchase intention. Furthermore, e-WOM is shown to positively and significantly influence brand image; however, its effect on repurchase intention is positive but not statistically significant. The results also indicate that brand image exerts a positive yet insignificant influence on repurchase intention. Overall, the study highlights the critical role of digital service quality in shaping customer perceptions and encouraging repeat purchases in the e-commerce sector. These findings provide managerial insights for e-commerce providers to prioritize service excellence in sustaining customer loyalty. Perkembangan layanan belanja daring menuntut perusahaan e-commerce untuk memberikan kualitas layanan digital yang andal serta membangun komunikasi elektronik yang efektif guna memperkuat citra merek dan mempertahankan pelanggan. Penelitian ini bertujuan menganalisis pengaruh e-service quality dan electronic word of mouth (e-WOM) terhadap brand image serta minat beli ulang pengguna Lazada di Kota Pekanbaru. Penelitian ini menggunakan pendekatan kuantitatif dengan menyebarkan kuesioner kepada 300 responden yang telah menggunakan platform Lazada dalam satu hingga tiga bulan terakhir. Data primer yang diperoleh dianalisis menggunakan metode Structural Equation Modeling berbasis Partial Least Square (SEM-PLS). Hasil penelitian menunjukkan bahwa e-service quality terbukti berpengaruh positif dan signifikan terhadap brand image serta minat beli ulang. Temuan lain mengindikasikan bahwa e-WOM berpengaruh positif dan signifikan terhadap brand image, namun tidak berpengaruh signifikan terhadap minat beli ulang. Sementara itu, brand image berpengaruh positif tetapi tidak signifikan terhadap minat beli ulang pengguna. Secara keseluruhan, penelitian ini menegaskan bahwa kualitas layanan digital memiliki peran dominan dalam mendorong terbentuknya citra merek yang kuat dan meningkatkan kecenderungan pelanggan untuk melakukan pembelian ulang pada platform e-commerce. Temuan ini memberikan implikasi manajerial bagi perusahaan e-commerce dalam memprioritaskan peningkatan kualitas layanan digital sebagai strategi mempertahankan pelanggan.